La propretura cesariana en la Hispania Ulterior: “La II guerra lusitana” - Novillo López, Miguel Ángel (Gerión. Revista de Historia Antigua, 2011)
The aim of this paper is to explain the parallels between the campaigns that Decimus Junius Brutus held in the Lusitanian area and northwest of roman Spain, and the operations that Julius Caesar leaded during his propraetorship in that territory. These agreements allow identifying the Caesarean propraetorship with a II Lusitanian War. However, Caesar did not practice campaigns of conquest but of punishment for the purpose of obtaining wills and boots, and impose new political-administrative patterns in the territory.